Active Carbon Flux of Mesozooplankton in South China Sea and Western Philippine Sea - Ge, Ruping; Chen, Hongju; Zhuang, Yunyun; Liu, Guangxing (Frontiers in Marine Science, 2021)
The active carbon flux mediated by diel vertical migration (DVM) of zooplankton is an important component of the downward carbon flux in the ocean. However, active fluxes transported by zooplankton DVM are poorly known in the South China Sea (SCS) and the Western Philippine Sea (WPS). In this study, active carbon fluxes in the SCS and WPS were evaluated on the basis of the data of mesozooplankton community and DVM at two stations of these areas. The mesozooplankton community in the SCS was obviously different from that in the WPS, and higher species number and abundance in the SCS were observed, which may be related to the higher chlorophyll a (Chl a) concentration and the wide gradients of temperature and salinity in this sea. Moreover, shallow depth Chl a maximum and strong thermocline were detected in the SCS, causing lower migration amplitudes of mesozooplankton in the SCS than those in the WPS. However, the migrant biomass of mesozooplankton in the SCS was 116.28 mg C m−2, higher than that in the WPS at 33.24 mg C m−2. The mesozooplankton active carbon flux in the SCS (11.28 mg C m−2·d−1) was also higher than that in the WPS (3.36 mg C m−2·d−1). The mesozooplankton active fluxes were equivalent to 12.9% and 14.1% of the total flux (active flux plus passive flux) of the SCS and WPS, respectively, and they play an important role in the biological pump functioning in the two regions.